A 2003 stratospheric aerosol extinction and PSC climatology from GOMOS measurements on Envisat - Vanhellemont, F.; Fussen, D.; Bingen, C.; Kyrölä, E.; Tamminen, J.; Sofieva, Viktoria; Hassinen, S.; Verronen, P.; Seppälä, A.; Bertaux, Jean-Loup; Hauchecorne, Alain; Dalaudier, Francis; et al. (HAL CCSD, 2005)
International audience Stratospheric aerosols play an important role in a number of atmospheric issues such as midlatitude ozone depletion, atmospheric dynamics and the Earth radiative budget. Polar stratospheric clouds on the other hand are a crucial factor in the yearly Arctic 5 and Antarctic ozone depletion. It is therefore important to quantify the stratospheric aerosol/PSC abundance. In orbit since March 2002, the GOMOS instrument onboard the European Envisat satellite has provided a vast aerosol extinction data set. In this paper we present an aerosol/PSC climatology that was constructed from this data set, together with a discussion of the results.